(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1993)
The first finding of a plesiosaur remain in Italy is reported. The specimen, a single humerus has been collected in the Argille Varicolori formation, in an outcrop close to the village ol Zavattarello near Varzi (Pavia, Lombardy, Northern Italy). Micropaleontological dating by analysis of calcareous nannofossils indicates a Santonian-Campanian age for the sediment enclosing the fossil. The morphology of the bone is described: available characters allow to consider the bone as belonging to a juvenile specimen and to ascribe it to the Plesiosauria with confidence, but the poor preservation prevents further reliable taxonomic assignment at lower ranks; some clues however suggest that it may belong to the Pliosauroidea.